Radiation therapy for synchronous oligometastatic Nasopharyngeal cancer in a low-middle-income country - Attia, Najla; Mousli, Alia; Ben zid, Khedija; Mokrani, Cyrine; Hammami, Rami; Ayadi, Hadhemi; Ghorbel, Asma; Yousfi, Amani; Kedous, Skander; Souheil, Jebali; Zaraa, Semia; Abidi, Rim; et al. (F1000 research, 2025)
Introduction Nasopharyngeal cancer, prevalent in Tunisia, is often diagnosed at an advanced stage. The therapeutic approach for metastatic forms has evolved with the concept of oligometastasis. Our study aims to evaluate the effectiveness of curative locoregional radiotherapy in these cases, with the objectives of estimating overall and progression-free survival and identifying prognostic factors. Methods This was a retrospective study, including 50 patients treated with curative radiotherapy for oligometastatic nasopharyngeal cancer from January 1st, 2015, to December 31, 2021, at the Salah Azaiez Institute. Results The mean age was 49.6 years, with a male predominance (72%). Initial symptoms were mainly rhinological (38%) and cervical lymphadenopathy (34%). Most patients presented with an advanced stage (T3-T4: 60%, N3: 52%). Metastases were most often osseous (46%), pulmonary (38%), or visceral (liver, extra-cervical lymph nodes: 16%). Thirty-six percent of patients had a single metastatic site, while 30% had more than two. All patients received platinum-based chemotherapy (3 cycles on average), followed by locoregional radiotherapy (70 Gy in 33-35 fractions), mainly with IMRT (76%). Concomitant chemotherapy was associated in 98% of cases. These treatments were associated with adverse effects, including radiodermatitis (100%) and mucositis (98%, including 18% grade 3). Twenty-four percent of patients received maintenance chemotherapy with capecitabine, and 44% received local treatment of metastases. At 3 years, progression-free survival (PFS) was 18% and overall survival (OS) was 44%. Univariate analysis showed a significant impact of several factors on PFS (gender, T stage, interruption of radiotherapy, maintenance chemotherapy). Multivariate analysis did not identify any independent prognostic factor for PFS. However, for OS, T stage (p = 0.024) and metastatic site (p = 0.001) emerged as independent prognostic factors. Conclusion This study served to evaluate radiotherapy practices; it would be even more interesting to conduct a larger-scale study.